Evaluation of Water Sorption and Solubility and FTIR Spectroscopy of Thermoplastic Orthodontic Retainer Materials Subjected to Thermoforming and Thermocycling - Alaa T. Albilali; Bashayer H. Baras; Mohammad A. Aldosari (Applied Sciences, 2023)
Due to the fact that retainers are often recommended for a lifetime, their endurance and longevity are directly related to the quality of the materials used in their production. Our study examined the water sorption, water solubility, and Fourier transform infrared (FTIR) spectroscopy of six commercially available thermoplastic retainer materials (Essix Plus, Zendura, Duran Plus, Tru-Tain DX, Imprelon S pd, and Essix ACE). Moreover, this study evaluated the effect of thermoforming and thermocycling on the water sorption and solubility and surface molecular composition of the tested materials. The present study found that the type of retainer material affected water sorption and solubility capabilities. In addition, the aging methods employed significantly affected some retainer materials’ water sorption and solubility. Moreover, the surface molecular composition evaluated by FTIR spectroscopy revealed that most of the evaluated materials had similar FTIR spectra except for Zendura. All materials had a spectrum that resembled polyethylene terephthalate glycol (PETG) while Zendura had a spectrum similar to semi-rigid polyurethane (PU). Only Zendura had relatively unstable surface structural composition evaluated under the effects of (thermoforming and thermocycling) compared to all tested materials.